Speech production differences in English and Italian speakers with nonfluent variant PPA. (10th March 2020) - Canu, Elisa; Agosta, Federica; Battistella, Giovanni; Spinelli, Edoardo G.; DeLeon, Jessica; Welch, Ariane E.; Mandelli, Maria Luisa; Hubbard, H. Isabel; Moro, Andrea; Magnani, Giuseppe; Cappa, Stefano F.; Miller, Bruce L.; et al.
Abstract : Objective: To understand whether the clinical phenotype of nonfluent/agrammatic primary progressive aphasia (nfvPPA) could present differences depending on the patient's native language. Methods: In this cross-sectional study, we analyzed connected speech samples in monolingual English (nfvPPA-E) and Italian speakers (nfvPPA-I) who were diagnosed with nfvPPA and matched for age, sex, and Mini-Mental State Examination scores. Patients also received a comprehensive neuropsychological battery. All patients and 2 groups of age-matched healthy controls underwent an MRI scan with 3D T1-weighted sequences. Connected speech measures and the other cognitive features were compared between patient groups. MRI variables, in terms of gray matter volume, were compared between each patient group and the corresponding controls. Results: Compared to nfvPPA-E, nfvPPA-I had fewer years of education and shorter reported disease duration. The 2 groups showed similar regional atrophy compatible with clinical diagnosis. Patients did not differ in nonlanguage domains, comprising executive scores. Connected speech sample analysis showed that nfvPPA-E had significantly more distortions than nfvPPA-I, while nfvPPA-I showed reduced scores in some measures of syntactic complexity. On language measures, Italian speakers performed more poorly on syntactic comprehension. Conclusions: nfvPPA-E showed greater motor speech impairment than nfvPPA-I despite higher level of education and comparable disease severity and atrophy changes. The data also suggest greater grammatical impairment in nfvPPA-I. This study illustrates the need to take into account the possible effect of the individual's spoken language on the phenotype and clinical presentation of primary progressive aphasia variants.